The Coptic Papacy in Islamic Egypt 641-1517 - Swanson, Mark N. (The American University in Cairo Press, 2022)
In Volume 1 of this series, Stephen Davis contended that the themes of "apostolicity, martyrdom, monastic patronage, and theological resistance" were determinative for the cultural construction of Egyptian church leadership in late antiquity. Building on recent advances in the study of sources for Coptic church history, the present volume aims to show how portrayals of the medieval popes provide a window into the religious and social life of their community. --
Keywords: Coptic Church / History; Coptic Church; Geschichte 641-1517; Coptic fathers of the church / History; Coptic monasticism and religious orders / Egypt; Coptic Christian saints; Coptic fathers of the church; Coptic monasticism and religious orders; Kopten; Egypt / Church history; Egypt; Ägypten